Konsentrasi Radon-222 dalam Gas Tanah untuk Deteksi Distribusi Permeabilitas di Daerah Panas Bumi Tampomas, Jawa Barat - Prasetio, Rasi; Laksminingpuri, Neneng; Pujiindiyati, Evarista Ristin (EKSPLORIUM, 2020)
Upflow zone in the geothermal system is a zone with high permeability that serves as a path for geothermal fluid to ascend to the surface, which usually marked with fumarole at the surface. Mount Tampomas, West Java, is a potential geothermal site with some thermal manifestation in the form of hot springs, but no fumarole or steam vent exists. The up-flow or the permeable zone is difficult to identify. 222Rn isotope is a radiogenic isotope that its concentration in soil gas can infer primary permeability as well as secondary permeability (structure). Series of 222Rn measurement in soil gas has been performed from 56 sampling positions around Mount Tampomas to evaluate 222Rn anomaly by a statistical method and its relation with high permeability area, geological structure, and geothermal manifestation. The measurement and statistical evaluation results show that 222Rn concentration clustered into low (background), high, and anomaly concentration. The background values in 16 places are below 825 Bq/m3, while a high level in 32 areas between 825–7688 Bq/m3 and anomaly in 8 places above 7688 Bq/m3. Most of the locations with high and anomaly 222Rn concentrations did not locate near a structure lineament. All measurements near hot springs have a high 222Rn and anomaly. Ciseupan hot spring is an exception which may indicate that the hot spring is discharged laterally (outflow). Furthermore, there is no indication of a correlation between 222Rn with the elevation of the measurement location. The process of 222Rn transfer from the reservoir to the surface is considered by the geothermal reservoir's gas carrier mechanism through permeable zones.